Plant 3D genomics: the exploration and application of chromatin organization. Issue 5 (4th March 2021) - Pei, Liuling; Li, Guoliang; Lindsey, Keith; Zhang, Xianlong; Wang, Maojun
Summary: Eukaryotic genomes are highly folded for packing into higher‐order chromatin structures in the nucleus. With the emergence of state‐of‐the‐art chromosome conformation capture methods and microscopic imaging techniques, the spatial organization of chromatin and its functional implications have been interrogated. Our knowledge of 3D chromatin organization in plants has improved dramatically in the past few years, building on the early advances in animal systems. Here, we review recent advances in 3D genome mapping approaches, our understanding of the sophisticated organization of spatial structures, and the application of 3D genomic principles in plants. We also discuss directions for future developments in 3D genomics in plants.